Food policy and consumption in Nicaragua, 1965-1995 - Berth, Christiane (2014)
The article analyses the most significant public debates related with food policy and consumption in Nicaragua. It focuses on three specific moments of Nicaraguan history: First, the period of the Somoza dictatorship, second the Sandinista revolution and third the neoliberal government of President Violeta Chamorro. In general, this paper reviews the perspectives of three groups: Nicaraguan governmental institutions and politicians, international organizations, and civil society.On the one hand, it explains hunger and malnutrition among the urban and rural poor; on the other hand it describes the forming of new consumption habits among the middle classes and elites, mainly in urban areas. The article is based on the reports of Nicaraguan government institutions, newspaper articles and studies of international organizations.